Presence of a wild-weed-crop complex in Phaseolus vulgaris L. in Peru? - Debouck, Daniel G.; Gamarra F., M.; Ortíz Arriola, V.; Tohme, Joseph M. (1989)
Mixtures of bean var. are cultivated in the Peruvian highlands in association with maize. Different wild types were found in abandoned fields in different areas. The presence of the wild types of P. vulgaris constitutes a basic generator of variability named the weed-crop complex. Field observations and biochemical studies of phaseollins and isozymes demonstrate that farmers know both the wild and the weed type forms of P. vulgaris, and that they sometimes use them to enrich the bean var. mixtures they cultivate. (CIAT)